Multi-model study of mercury dispersion in the atmosphere: Atmospheric processes and model evaluation - Travnikov, Oleg (2017)
Current understanding of mercury (Hg) behaviour in the atmosphere contains significant gaps. Some key characteristics of Hg processes including anthropogenic and geogenic emissions, atmospheric chemistry, and air-surface exchange are still poorly known. This study provides a complex analysis of processes governing Hg fate in the atmosphere involving both measurement5 data from ground-based sites and simulation results of chemical transport models. A variety of long-term measurements of gaseous elemental Hg (GEM) and reactive Hg (RM) concentration as well as Hg wet deposition flux has been compiled from different global and regional monitoring networks. Four contemporary global-scale transport models for Hg were applied both in their state-of-the-art configurations and for a number of numerical experiments aimed at evaluation of particular processes.